Cosmological model with perfect fluid - O. O. Iegurnov; M. P. Korkina (Вісник Астрономічної школи, 2012)
The cosmological model with perfect fluid is considered. We suppose that this model is homogeneous and anisotropic. The analysis of the spatial curvature tensor invariants showed that they have no singularities and depends on arbitrary function ζ(t) and have no singularities. Construction of the model is based on the following boundary conditions: 1) As initial conditions we choose the Big Bang, the corresponding Friedman model. We also suppose that at initial moment of time we have ultrarelativistic state equation. 2) When t→∞ describing metric turns into Robertson–Milne metric.